Noise, voice and silencing during immigrant court-case performances in Swedish district courts. (October 2017) - Elsrud, Torun; Lalander, Philip; Staaf, Annika
This article argues that court-ritual unawareness, linguistic shortcomings and stereotypical images about non-Swedish otherness impair the position and acting space for immigrants in a Swedish district court context. Drawing on two ethnographically informed research projects focused on courtroom interaction during more than 20 trials dealing with 'domestic violence' and 'street-related crime', we claim that immigrant voices are often silenced due to taken-for-granted practices in court. Through analyses of interviews, performances, interpreted hearings and references to a desirable Swedishness, it is argued that situations are created where immigrant participants may experience their possibility of being understood as limited and their voices as being unheard. Such conditions are emotionally draining and may result in participants choosing silence over stating their case. This is a problem, not only within the individual court case, but also for the overall legitimacy of the court system and for issues of institutional trust among citizens.